Human Population Competition: A Study of the Pursuit of Power through Numbers, Symposium Series 46 A - Kadankavil, Thomas (Journal of Dharma, 1999)
Jack Parsons, Human Population Competition. A Study of the Pursuit of Power through Numbers, Symposium Series 46A, Lewiston, Queenstown, Lampeter: The Edwin Mellen Press, 1998, pp.xvii+432. (ISBN 0-7734-8372-1).